Tissue engineering with adult stem cells in reconstructive surgery (Review) - Gößler, Ulrich; Hörmann, Karl; Riedel, Frank (International journal of molecular medicine, 2005)
Tissue engineering is a multidisciplinary field combining biology and engineering along with clinical application to design, manufacture, modify, grow and maintain living tissue. This field has enjoyed tremendous growth in the past 10 years fueled by its potential role in regenerating new tissues and naturally healing injured or diseased organs. Many approaches to tissue engineering have been explored, including ex vivo de novo construction of tissues and strategies of in vivo induction of tissue regeneration. Interventions are hindered by factors such as rejection by the immune system, limited blood supply or morbidity of the donor site. Regardless of the approach, most researchers and clinicians agree that any successful tissue engineering construct will derive from a single unit, the cell. Because the engineering of tissue necessitates a sufficient number of tissue-specific cells with minimal donor site morbidity, a great deal of scientific effort has been directed towards stem cell research and the use of stem cells as a source of cells for new tissues. This review aims at outlining the role of stem cells in tissue engineering, focusing on the use of adult-derived stem cells as applied to the research and practice of plastic surgery.
Gesehen am 01.04.2022